SHF, SSF, and co-fermentation of alkali and steam delignified agro-residues to bioethanol - Shankarappa T. H.; Geeta G. S.; Patil C. R.; Alagawadi A. R.; Jagadeesh K. S. (Maejo International Journal of Energy and Environmental Communication, 2025)
Five agro-residues, including sugarcane bagasse, sugarcane tops, sugarcane trash, corn husk and corn stover, were tested for bioethanol production by different fermentation methods using alkali-pretreated, enzymatically saccharified substrates. Co-fermentation of S. cerevisiae and C. shehatae was found to be more efficient in the bioethanol production than SHF and SSF. S. cerevisiae and C. shehatae complemented one another in the fermentation of hexose and pentose sugars. Together, these organisms had the highest ethanol yields from substrates: sugarcane bagasse (278.40 mg/g), sugarcane tops (262.75 mg/g), sugarcane trash (241.42 mg/g), corn husk (232.36 mg/g) and corn stover (239.82 mg/g). A scaled-up study was also carried out for sugarcane bagasse in optimised conditions. 1) 3.0% NaOH treatment (8 hours at room temperature) followed by autoclaving at 121oC for 1 hour. 2) Saccharification by cellulase enzymes (cellulase 15 FPU/g, b-glucosidase 10 IU/g and xylanase 5 U/g). 3) Fermentation by dual cultures (S. cerevisiae and C. shehatae). One kilogramme of pre-treated sugarcane bagasse with a 5% substrate concentration yielded 223 grammes of ethanol, 22.30 percent (w/w) of the pre-treated substrate.